2019
DOI: 10.2298/sos1902175t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticless in the structure and mechanical properties of mullite/Ag cermets

Abstract: The objective of this work was to study the influence of the addition of silver nanoparticles in the microstructure of mullite at two different temperatures of sintering (1500 and 1600 °C), in order to decrease the porosity and increase the density as well better the hardness and fracture toughness. The microstructural characteristics were studied by scanning electron microscopy, confocal scanning microscopy and X-ray diffraction. Mullite/Ag cermets with homogenous microstructure were and a fracture toughness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Few studies were found in the literature on the reinforcement of mulite by metals and only one research studied silver as a reinforcing medium. 15 For this reason and due to the high ductility of Ag allowing its usage as the reinforcing material, in this study we propose the processing of a new type of composite material based on mullite reinforced with silver particles.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies were found in the literature on the reinforcement of mulite by metals and only one research studied silver as a reinforcing medium. 15 For this reason and due to the high ductility of Ag allowing its usage as the reinforcing material, in this study we propose the processing of a new type of composite material based on mullite reinforced with silver particles.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these outstanding properties include; excellent thermal and chemical stability, high refractoriness and low creep rate [3][4]. The aluminosilicate mullite also has a low coefficient of thermal expansion and a very high thermal shock resistance [5][6]. Its usage and applications in high temperature industrial process and refractory applications have made the demand for this aluminosilicate increase day by day.…”
Section: Introductionmentioning
confidence: 99%